2018
DOI: 10.1155/2018/8916035
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity Influences Corpus Callosum Dimensions

Abstract: Background and Objective Corpus callosum (CC), the main white matter cable which connects two hemispheres of brain, is important in special procedures such as stereotaxic surgeries vary in size, in different populations. Determination of possible size differences in ethnical groups has special values. Patients and MethodsThe size of the CC on midsagittal view was determined in 76 normal male subjects using MRI of brain hemispheres in northern Iran. The size of rostrum, body, splenium, length, and height of CC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…With regard to racial comparisons, this study supports the concept that CC dimensions may vary across different ethnic and racial populations. This is comparable to what was reported by Nouri Hosseini et al (2018), who highlighted that ethnicity may influence CC dimensions. However, it is very difficult to draw a solid conclusion regarding the racial variations in CC from our comparison study due to the presence of several limitations.…”
Section: Discussionsupporting
confidence: 91%
“…With regard to racial comparisons, this study supports the concept that CC dimensions may vary across different ethnic and racial populations. This is comparable to what was reported by Nouri Hosseini et al (2018), who highlighted that ethnicity may influence CC dimensions. However, it is very difficult to draw a solid conclusion regarding the racial variations in CC from our comparison study due to the presence of several limitations.…”
Section: Discussionsupporting
confidence: 91%
“…Race and ethnicity have both been associated with unique phenotypic traits. For example, studies have observed significant differences in the corpus callosum between sub-populations of the Middle East (Allouh et al 2020 ; Hosseini et al 2018 ). In a study comparing brain volumes from healthy White ( n = 44) and Black or African American ( n = 25) individuals, volumetric differences were observed in the left orbitofrontal cortex (Isamah et al 2010 ).…”
Section: Challenges In Reporting Race and Ethnicity In Biomedical Res...mentioning
confidence: 99%
“…Health disparities, disease presentation, and patient outcomes are influenced by a wide range of factors including sex, race, and ethnicity (Tang et al 2022 ; Shakeshaft et al 2022 ; Nahar et al 2022 ; Tseng, et al 2020 ). In biomedical and neuroimaging research, differences across demographic groups have been observed in brain structure, anatomy, morphometry, connectivity, development, and disease (Allouh et al 2020 ; Bonkhoff et al 2021 ; Chand et al 2017 ; Delvecchio et al 2021 ; Giedd et al 2012 ; Hosseini et al 2018 ; Liu et al 2020 ). Despite documented differences between demographic groups, historical underrepresentation of minority and female participants has resulted in clinical and biomedical best practices informed by conclusions made using a narrow subset of the population (Brady et al 2021 ; Sardar et al 2014 ; Clayton and Collins 2014 ).…”
mentioning
confidence: 99%
“…The corpus callosum (CC) is the largest inter-hemispheric white matter tract in the human brain and is characterized by variations in morphology among individuals of different gender and race [ 8 , 10 , 14 , 16 , 17 ]. This MRI-based morphometric study of the CC was carried out in southeastern Nigeria.…”
Section: Discussionmentioning
confidence: 99%